Optimal economical dose of nitrogen and diagnostic leaf to assess the nutritional status of cowpea (Revista de Ciências Agroveterinárias, 2022)
Considering that crop nutrition is essential to obtain high yields, the objective of this study was to determine the optimal economical dose of nitrogen (N) associated with maximum technical and economical yield. Additionally, to correlate cowpea cultivars with N contents and yield. The experiment was conducted under the edaphoclimatic conditions of Teresina, PI, Brazil, in Entisol (Fluvic Neosol), in the second half of 2017, in a randomized block design in a factorial scheme (2x2x5), whose factors were: (i) cowpea genotypes (BRS Imponente and BRS Itaim), (ii) form of application of N fertilization (basal + top-dressing or fully top-dressing) and (iii) N doses (zero, 10, 30, 50 and 70 kg ha-1 - urea as source). The variables measured were the total N content in the plant tissue, with a collection of leaves +1 and +3, and grain yield. When analyzing the effect of the interaction, there was significance only for the factors form of application and N doses. However, when the doses were further analyzed for each form of N fertilization, the best response model was the quadratic, whose point of maximum physical yield was verified with N doses of 34 and 44 kg ha-1 for basal + top-dressing and fully top-dressing applications, respectively. Furthermore, the most economical doses for basal + top-dressing and fully top-dressing N applications were 26.0 and 35.6 kg ha-1, respectively. For N, the leaf that best represents the nutritional status for leaf diagnosis was +3.
Keywords: Topdressing fertilization; Starter fertilizaton; Vignaunguiculata